2016
DOI: 10.5539/ijef.v8n3p40
|View full text |Cite
|
Sign up to set email alerts
|

Financial Deepening and Domestic Investment in Nigeria

Abstract: The study examined the relationship between financial deepening and investment in Nigeria. Secondary data spanning from 1970 to 2013 was used for the empirical analysis. It adopted the Gregor-Hansen Endogenous structural break methodology and the supply-leading hypothesis in building the model. The study also employed the Unit Root Test, Co Integration Test and Granger Causality Test. It discovered a unidirectional causality, running from financial deepening to investment. It also found that the financial deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The causal relationship between the financial inclusion and agricultural sector output in Nigeria has more indication for independent causality hypothesis. This is in conformity with the conclusion of Demetriades and Hussein (1996), Obafemi et al (2016) and Aye (2015). Though it does not agree with the a priori expectation but it does solidify the result of Error Correction Model (ECM) which revealed that DR, PLR, ACGSF, DDR and PLSE with P-value of 0.2717, 0.0927, 0.6080, 0.4361 and 0.0565 respectively do not have any significant effect on agricultural sector output in Nigeria within the period of study.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…The causal relationship between the financial inclusion and agricultural sector output in Nigeria has more indication for independent causality hypothesis. This is in conformity with the conclusion of Demetriades and Hussein (1996), Obafemi et al (2016) and Aye (2015). Though it does not agree with the a priori expectation but it does solidify the result of Error Correction Model (ECM) which revealed that DR, PLR, ACGSF, DDR and PLSE with P-value of 0.2717, 0.0927, 0.6080, 0.4361 and 0.0565 respectively do not have any significant effect on agricultural sector output in Nigeria within the period of study.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…Fan and Dickie (2000) concluded that foreign direct investment (FDI) inflow stabilized the ASEAN-5 economies during the Asian financial crises. Obafemi et al (2016) examined the effect of financial deepening on domestic investment using financial deepening variables, such as banking spread and real interest rate from 1970 to 2013 and concluded that these factors exert a significant impact on investment. Using data from the Ghanaian economy, Musah et al (2018) examined the effect of FDI on the profitability of commercial banks and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, compared to related studies, this study differs in three main aspects. First, we investigate stability in the banking industry as a function of investment dynamics instead of reverse inquiry often found in the literature (Ndikumana, 2005; Obafemi et al , 2016). Second, we verify how MU may moderate such a relationship; and finally, we ascertain the role of governance in the surmised relationship between the stability of the banking industry and investment growth.…”
Section: Introductionmentioning
confidence: 99%
“…The banking sector innovations in the financial delivery and inclusivity has displayed an increasing trend in recent years leading to increase in money supply in the economy. Besides financial deepening mobilizes savings into investment projects, and also increases the marginal productivity of capital through the intermediation function of well-informed financial institutions (Obafemi, Oburota & Amoke, 2016). In Kenya, based on the theoretical backgrounds, M-Pesa stands tall as one of the revolutionists enabling over 90% of the citizens to benefit from the transaction platform (McGath, 2018;Misati et al, 2021).…”
Section: B Financial Deepening Theorymentioning
confidence: 99%